Aerobic Metabolism in Vibrio cholerae Is Required for Population Expansion during Infection - Andrew J. Van Alst (American Society for Microbiology, 2020)
ABSTRACT Vibrio cholerae replicates to high cell density in the human small intestine, leading to the diarrheal disease cholera. During infection, V. cholerae senses and responds to environmental signals that govern cellular responses. Spatial localization of V. cholerae within the intestine affects nutrient availability and metabolic pathways required for replicative success. Metabolic processes used by V. cholerae to reach such high cell densities are not fully known. We sought to better define the metabolic traits that contribute to high levels of V. cholerae during infection. By disrupting the pyruvate dehydrogenase (PDH) complex and pyruvate formate-lyase (PFL), we could differentiate aerobic and anaerobic metabolic pathway involvement in V. cholerae proliferation. We demonstrate that oxidative metabolism is a key contributor to the replicative success of V. cholerae in vivo using an infant mouse model in which PDH mutants were attenuated 100-fold relative to the wild type for colonization. Additionally, metabolism of host substrates, including mucin, was determined to support V. cholerae growth in vitro as a sole carbon source, primarily under aerobic growth conditions. Mucin likely contributes to population expansion during human infection as it is a ubiquitous source of carbohydrates. These data highlight oxidative metabolism as important in the intestinal environment and warrant further investigation of how oxygen and other host substrates shape the intestinal landscape that ultimately influences bacterial disease. We conclude from our results that oxidative metabolism of host substrates is a key driver of V. cholerae proliferation during infection, leading to the substantial bacterial burden exhibited in cholera patients. IMPORTANCE Vibrio cholerae remains a challenge in the developing world and incidence of the disease it causes, cholera, is anticipated to increase with rising global temperatures and with emergent, highly infectious strains. At present, the underlying metabolic processes that support V. cholerae growth during infection are less well understood than specific virulence traits, such as production of a toxin or pilus. In this study, we determined that oxidative metabolism of host substrates such as mucin contribute significantly to V. cholerae population expansion in vivo. Identifying metabolic pathways critical for growth can provide avenues for controlling V. cholerae infection and the knowledge may be translatable to other pathogens of the gastrointestinal tract.